Transient receptor potential ankyrin 1 promoter methylation and peripheral pain sensitivity in Crohn's disease - Gombert, Sara; Rhein, Mathias; Winterpacht, Andreas; Münster, Tino; Hillemacher, Thomas; Leffler, Andreas; Frieling, Helge (Clinical Epigenetics, 2019)
Background Crohn's disease is a chronic inflammatory disorder of the gastrointestinal tract associated with abdominal pain and diarrhea. Pain caused by Crohn's disease likely involves neurogenic inflammation which seems to involve the ion channel transient receptor potential ankyrin 1 (TRPA1). Since the promoter methylation of TRPA1 was shown to influence pain sensitivity, we asked if the expression of TRPA1 is dysregulated in patients suffering from Crohn's disease. The methylation rates of CpG dinucleotides in the TRPA1 promoter region were determined from DNA derived from whole blood samples of Crohn patients and healthy participants. Quantitative sensory testing was used to examine pain sensitivities. Results Pressure pain thresholds were lower in Crohn patients as compared to healthy participants, and they were also lower in females than in males. They correlated inversely with the methylation rate at the CpG - 628 site of the TRPA1 promoter. This effect was more pronounced in female compared to male Crohn patients. Similar results were found for mechanical pain thresholds. Furthermore, age-dependent effects were detected. Whereas the CpG - 628 methylation rate declined with age in healthy participants, the methylation rate in Crohn patients increased. Pressure pain thresholds increased with age in both cohorts. Conclusions The TRPA1 promoter methylation appears to be dysregulated in patients suffering from Crohn's disease, and this effect is most obvious when taking gender and age into account. As TRPA1 is regarded to be involved in pain caused by neurogenic inflammation, its aberrant expression may contribute to typical symptoms of Crohn's disease.
CRIS-Team WoS Importer:2020-01-10